Did attending P.A.R.T.Y. change youth perceptions? Results from 148 Queensland schools participating in the Prevent Alcohol and Risk-Related Trauma in Youth Program, 2018–2019. Issue 3 (19th October 2021) - Cameron, Cate M; Eley, Rob; Judge, Chantelle; O'Neill, Roisin; Handy, Michael
Abstract : Background: Prevent Alcohol and Risk-Related Trauma in Youth (P.A.R.T.Y.) is an immersive 1 day in-hospital injury awareness and prevention programme designed to educate high-school students on the consequences of a variety of risk-taking behaviours. This multisite contemporary analysis examined differences in programme effect and temporal changes on participant knowledge and attitudes. Methods: Metropolitan and rural schools were invited to attend the programme at one of the 11 hospital sites throughout Queensland, Australia. Pre–post study design with participant questionnaires provided at three time periods: immediately preprogramme and postprogramme, and 4 months later. The questionnaire used scenarios to determine a participant's opinion on the safety of drugs/alcohol, driving and risk-taking activities, using Likert scales. Results: A total of 5999 students participated in the programme between 1 January 2018 and 31 December 2019. Responses to all questions related to safety, harm or risk followed a similar pattern. The immediate postcourse responses demonstrated significant increased awareness of risk or change in action, followed by a decay at 4 months to within 10% of preprogramme levels. Public school students, males and students from Central and North Queensland demonstrated lower risk-aversion (p<0.05). Conclusion: This study demonstrated across more than 100 school sites, the positive change in knowledge and student participant attitudes towards risk-taking behaviours after attending the P.A.R.T.Y. programme. The need to address the significant decay at the 4-month follow-up was identified. Findings offered potential for tailoring of messaging to target key demographic groups/topics where the decay was greatest.